PENDISTRIBUSIAN KEADILAN OLEH PENGADILAN SERTA BUDAYA HUKUM DALAM PENYELESAIAN SENGKETA - Suparman, Eman (Jurnal Hukum dan Peradilan, 2012)
Handle civil disputes in general, for many the sense how the courts considered too laden with procedures, formalistic, rigid, and slow to make a decision on a dispute. Presumably these factors can not be separated from the judge's perspective on a very rigid laws and normative-procedural law in doing concretization. While a judge should be able to be living interpretator captures the spirit of fairness in society and not bound by the normative-procedural rigor present in a legislation, because the judge is no longer a la bouche de la loi (law funnel). There are indications that the judge did not have enough courage to make decisions that are different from the normative provisions of the law, so that substantial justice is always difficult to achieve through a court verdict, because the judges and the courts will only give formal justice. Assessment of fairness in general terms only from one side only, ie those who receive treatment. The seekers of justice in general, defeated parties in the case, will always provide an assessment that the unjust verdict. It can not be denied is one result of the function and role of the trial run has been oriented towards the success of efforts to support and programs set by the government or the executive. Keywords: normative procedural, formal justice, substantial justice